2019
DOI: 10.4314/ijs.v21i1.2
|View full text |Cite
|
Sign up to set email alerts
|

Integrated geophysical methods and techniques for siting productive boreholes in basement complex terrain of southwestern Nigeria

Abstract: Electrical resistivity survey involving 2D Dipole-Dipole subsurface imaging and 1D Vertical Electrical Sounding (VES) and an integrated magnetic and electrical resistivity survey involving magnetic profiling and 1D VES/2D electrical imaging techniques were carried out at two sites underlain by grey gneiss and pegmatised schist, respectively, within the Obafemi Awolowo University, Ile-Ife, Osun State, Nigeria. The surveys were carried out with a view to delineating the subsurface layers and determining the geoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 10 publications
(10 reference statements)
0
20
0
Order By: Relevance
“…Hydrogeological studies of the pre-Cretaceous Basement Complex Formations of Nigeria (Akinluyi et al 2018;Anderson and Ogilbee 1973;Olorunfemi and Oni 2019), revealed an average borehole yield of 14.67 gallons per sec (gps) from a mean depths of 37.49 m. Though, few boreholes in the unweathered rock, typically granite or gneiss produced more than a meager amount of water; in many wells, no water was found (Anderson and Ogilbee 1973). In contrast, wells tapping weathered granite and gneiss, where fully saturated, are found to yield the highest quantity of water (51.67 gps); the average yield for boreholes tapping battered rock was estimated to be around 23.33 gps per borehole (Anderson and Ogilbee 1973).…”
Section: Hydrogeological Settingmentioning
confidence: 99%
See 4 more Smart Citations
“…Hydrogeological studies of the pre-Cretaceous Basement Complex Formations of Nigeria (Akinluyi et al 2018;Anderson and Ogilbee 1973;Olorunfemi and Oni 2019), revealed an average borehole yield of 14.67 gallons per sec (gps) from a mean depths of 37.49 m. Though, few boreholes in the unweathered rock, typically granite or gneiss produced more than a meager amount of water; in many wells, no water was found (Anderson and Ogilbee 1973). In contrast, wells tapping weathered granite and gneiss, where fully saturated, are found to yield the highest quantity of water (51.67 gps); the average yield for boreholes tapping battered rock was estimated to be around 23.33 gps per borehole (Anderson and Ogilbee 1973).…”
Section: Hydrogeological Settingmentioning
confidence: 99%
“…3 The geological cross section of Sokoto Basin and the normal depth to water stand at about 6 m (Anderson and Ogilbee 1973). Generally, groundwater condition in the basement section of Sokoto Basin is typical of the Nigerian Basement Complex described by (Akinluyi et al 2018;Olorunfemi and Oni 2019).…”
Section: Hydrogeological Settingmentioning
confidence: 99%
See 3 more Smart Citations